Letter from R.E. Preston to Margaret M. Booth, March 7, 1890 - Preston, Robert E., 1836–1911 (1890)
Letter from Robert E. Preston (1836-1911), of the United States Mint Bureau, to Margaret M. Booth née Cardeza enclosing a copy of a contract for the services of a lawyer, Mr. Baker, for Mrs. Booth to sign and return.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States